Abraham versus Jakub - Lemański, Janusz (Collectanea Theologica, 2019)
This article deals with the process of the formation of the traditions concerning the three patriarchs in the book of Genesis. It can already be stated that the traditions concerning Abraham, Isaac, and Jacob were initially formed independently of each other. Chronological priority should be assigned to the tradition concerning Jacob. It was originally somehow combined with the tradition concerning Isaac (in Amos), and at the time before the exile it constituted the earliest point of reference for seeking the roots and identity of Israel. Only by the end of the exile did the particular time and situation cause the local Judaean traditions concerning Abraham to play a greater role also from a theological aspect. Abraham then became not only a model of faith and an example of behaviour for the exiles and the repatriates, but also from a the first link in the chain of the three patriarchs. It is possible that at that time some of the motifs of the story of Abraham were borrowed from the traditions concerning Isaac (cf. Gen 26).